2011
DOI: 10.1148/rg.315115003
|View full text |Cite
|
Sign up to set email alerts
|

How to Differentiate Benign versus Malignant Cardiac and Paracardiac18F FDG Uptake at Oncologic PET/CT

Abstract: Patients undergoing 2-[fluorine 18]fluoro-2-deoxy-d-glucose (FDG) whole-body oncologic positron emission tomography (PET)/computed tomography (CT) are studied while fasting. Cardiac FDG uptake in fasted patients has been widely reported as variable. It is important to understand the normal patterns of cardiac FDG activity that can be seen in oncologic FDG PET/CT studies. These include focal and regional patterns of increased FDG myocardial activity. Focal activity can be observed in papillary muscles, the atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 59 publications
3
62
0
6
Order By: Relevance
“…Our findings on analyzing the patterns of 18 F-FDG distribution in physiologically nondiffuse cardiac uptake (score of 3) are in keeping with earlier publications (22)(23)(24). Knowledge of these variable patterns of nonpathologic uptake is important in the interpretation of 18 F-FDG PET scans for cardiac inflammatory or infectious disease when cardiac suppression may not be adequate.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on analyzing the patterns of 18 F-FDG distribution in physiologically nondiffuse cardiac uptake (score of 3) are in keeping with earlier publications (22)(23)(24). Knowledge of these variable patterns of nonpathologic uptake is important in the interpretation of 18 F-FDG PET scans for cardiac inflammatory or infectious disease when cardiac suppression may not be adequate.…”
Section: Discussionsupporting
confidence: 92%
“…6 Nonspecific findings that may indicate failed suppression, and/or physiologic uptake and make image interpretation challenging included diffuse myocardial activity exceeding liver uptake or uptake in the lateral wall and/or ring shaped/circumferential basal uptake (Nensa et al doi: 10.1007/s12350-016-0443-1) 7 or papillary muscle uptake. 8,9 Diffuse FDG uptake in the entire left ventricular wall without focal uptake generally does not indicate disease as cardiac sarcoidosis is histopathologically known to be localized and not diffuse. 10 Absence of contrast enhancement, edema, or wall motion abnormalities on cardiac MRI associated with these nonspecific FDG uptake patterns is useful in avoiding false positive interpretations (Nensa et al doi:10.1007/s12350-016-0443-1).…”
Section: See Related Article Pp 86-99mentioning
confidence: 99%
“…During oncologic imaging, the required patient's fasting forces the heart to use free fatty acid as substrate and should result in low and uniformed cardiac uptake features [7] . In real practice, the cardiac uptake patterns are variable even in serial PET exams of the same patient.…”
Section: Physiologic Variantsmentioning
confidence: 99%
“…Furthermore, new perfusion defects may appear 3 to 6 years post-treatment in patients who had initially normal cardiac SPECT scans after treatment [23,24] . It has been suggested that a radiation dose greater than 35 Gy is required to result in increased FDG activity [7] (see Figure 14). Talc pleurodesis is a procedure to treat persistent pneumothorax or recurrent pleural effusion.…”
Section: Trauma Iatrogenic and Post-procedural Changesmentioning
confidence: 99%